MULTIMEDIA-ENHANCED ROLE-PLAY AS A PEDAGOGICAL STRATEGY TO IMPROVE SPEAKING SKILLS: AN ACTION RESEARCH STUDY - Harpiansi, Harpiansi; Prima, Anggra; Purwanto, M Bambang (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study aims to explore and evaluate the effectiveness of integrating role-play methods and multimedia technology in enhancing English speaking skills among students in the hospitality industry context. Using an action research approach, this study was conducted in the third semester of students majoring in travel business at Prasetiya Mandiri Polytechnic, Bogor. This research method includes three cycles of action: planning, action, observation, and reflection. In the planning stage, role-play scenarios relevant to real situations in the hospitality industry are designed and combined with multimedia technologies such as video tutorials, interactive simulations, and language learning software. Students then participate in role-play activities integrated with these multimedia elements. The results showed that integrating role-play and multimedia technology significantly improved students' speaking skills. Students become more confident in using English, can communicate more effectively, and show improvement in aspects of pronunciation, intonation, and proper use of vocabulary. This study concludes that integrating role-play with multimedia technology is a practical approach to improving English speaking skills among hospitality students. The practical implications of these findings suggest the application of similar methods in language training curricula in other industries, as well as recommendations for further development of technology-based learning aids to support contextual and interactive language learning.